2016
DOI: 10.1088/1054-660x/26/5/056202
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of a laser pulse and electro-optic switch in a GaAs/AlGaAs quadruple-coupled quantum dot molecule nanostructure

Abstract: Based on a GaAs/AlGaAs quadruple-coupled quantum dot heterostructure, an optical switch for controlling superluminal and subluminal light propagation is suggested. The transient and steady state behaviour of the absorption and dispersion of a probe pulse laser field through a quadruple quantum dot molecule are studied. We show that the group velocity of a light pulse can be controlled from superluminal to subluminal, or vice versa, by controlling the tunnelling rates between the quantum dots. The required swit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Subluminal and superluminal light propagation has been discussed in various atomic systems and it has been shown that switching from subluminal to superluminal (or vice versa) can be achieved with the intensity of coupling fields, the relative phase of applied fields and an incoherent pumping field [19][20][21][22]. In addition, a new model for controlling the optical properties of the light pulse via the quantum coherence Laser Physics Slow and fast light propagation and controllable switch at λ = 1.55 µm in a photonic crystal with a defect layer doped by an InAs/GaAs quintuple-coupled quantum dot molecule nanostructure effect in a semiconductor heterostructure was proposed very recently [23][24][25][26][27]. It was noted that the incoherent pumping field and the tunneling effect can be used as potential parameters for adjusting the transient and steady-state behavior of light beams [27].…”
Section: Introductionmentioning
confidence: 99%
“…Subluminal and superluminal light propagation has been discussed in various atomic systems and it has been shown that switching from subluminal to superluminal (or vice versa) can be achieved with the intensity of coupling fields, the relative phase of applied fields and an incoherent pumping field [19][20][21][22]. In addition, a new model for controlling the optical properties of the light pulse via the quantum coherence Laser Physics Slow and fast light propagation and controllable switch at λ = 1.55 µm in a photonic crystal with a defect layer doped by an InAs/GaAs quintuple-coupled quantum dot molecule nanostructure effect in a semiconductor heterostructure was proposed very recently [23][24][25][26][27]. It was noted that the incoherent pumping field and the tunneling effect can be used as potential parameters for adjusting the transient and steady-state behavior of light beams [27].…”
Section: Introductionmentioning
confidence: 99%
“…furthermore, it has been shown that quantum interference arising from SGC [8] and incoherent pumping field [17] can be used for analyse of some interesting phenomena such as lasing without population inversion [4], optical bistability [17], and superluminal/subluminal light propagation [18]. Similar phenomena involving quantum coherence in solid state systems such as semiconductor quantum wells (QWs) and quantum dots (QDs) [19], can also be occurred [20,21]. In the past decade, there has been an increasing interest in optical properties of quantum dot molecules (QDMs) and quantum wells (QWs), due to important role in optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been shown that quantum interference arising from SGC [8] and incoherent pumping field [18] can be used for analyse of some interesting phenomena such as lasing without population inversion [5], optical bistability [18], and superluminal/ subluminal light propagation [19]. Similar phenomena involving quantum coherence in solid state systems such as semiconductor quantum wells (QWs) and quantum dots (QDs) [20], can also be occurred [21,22]. In the past decade, there has been an increasing interest in optical properties of quantum dot molecules (QDMs) and quantum wells (QWs), due to important role in optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%